Indigenous entrepreneurship, ¿An economic dimension of Sumak Kawsay? - Carmen Amelia Coral Guerrero (AECOOP Escuela de Estudios Cooperativos, 2019)
The world's indigenous population suffers poverty and exclusion, and there is little literature that addresses the economic component from its worldview; particularly in Latin America from the perspective of good living. The objectives of this article are to determine the economic elements of Sumak Kawsay as an alternative to development, and the contributions of indigenous entrepreneurship to their community through a qualitative approach in the Ecuadorian Amazon. We build our results based on information obtained through 22 semistructured interviews in the context of the cooperative of 850 families from the Kallari community, dedicated mainly to the production, marketing and export of organic cocoa and fine aroma chocolate. Participation, food sovereignty and the fight against poverty are the result of the joint work of Kallari, which serves as a guide for other indigenous communities to strengthen their organizations with periphery-center approaches. The study concludes with the importance of the sustainability of the project, calling the attention to the governments on the importance of the political participation of the indigenous communities in the construction of public policies focused on the specific needs of their territories.